2021
DOI: 10.1002/admt.202100405
|View full text |Cite
|
Sign up to set email alerts
|

A Lithium‐Silicon Microbattery with Anode and Housing Directly Made from Semiconductor Grade Monocrystalline Si

Abstract: The development of systems that can economically convert and store electricity, preferably from solar energy, are urgently needed to address the numerous problems humankind is faced with in the centuries to come. [1] Lithium-ion batteries belong to the family of devices that take advantage of electrochemical reactions to store energy. [2][3][4][5][6] Because of its light weight and the fact that Li + ions are fast and small charge carriers, the development of lithium-ion batteries is a success story par excell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…The small footprint (0.09 cm 2 ) Li-ion MB [ Figure 6E and F] presented an initial discharge capacity of 5.2 mWh cm -2 and a reversible capacity of 1.6 mWh cm -2 after 100 cycles with an average Coulombic efficiency of above 92%. Similarly, laser-patterned Si/TiN/Ge [63] , self-standing porous Si films [64] , plasma-etched Si/TiN/Sb nanorod arrays [65] , and dry etching Si towers [66] have also been reported for high-energy Li-ion MBs by accommodating the volume expansion of Si materials.…”
Section: Structural Design For Microbatteries: From 2d To 3d Assemblymentioning
confidence: 96%
“…The small footprint (0.09 cm 2 ) Li-ion MB [ Figure 6E and F] presented an initial discharge capacity of 5.2 mWh cm -2 and a reversible capacity of 1.6 mWh cm -2 after 100 cycles with an average Coulombic efficiency of above 92%. Similarly, laser-patterned Si/TiN/Ge [63] , self-standing porous Si films [64] , plasma-etched Si/TiN/Sb nanorod arrays [65] , and dry etching Si towers [66] have also been reported for high-energy Li-ion MBs by accommodating the volume expansion of Si materials.…”
Section: Structural Design For Microbatteries: From 2d To 3d Assemblymentioning
confidence: 96%
“…4a compares the areal energy density of various microbatteries. 23,[45][46][47][48][49][50][51] Microbatteries have two common architectures: layered thin films and interdigitated electrode strips on the surface. [45][46][47] Despite the high attainable energy density, they are larger than 1 mm 2 because of difficulties in shrinking the size, such as maintaining the structural integrity with a small footprint and accuracy of layering down tiny films.…”
Section: Electrochemical Performance Of Microbatterymentioning
confidence: 99%
“…Moreover, the SEI layer on the surface of Si particle bursts due to the volume expansion of Si, which makes Si react with electrolyte continuously, resulting in continuous consumption of active lithium and eventually capacity loss. [84][85] Sternad's group prepared micro-LIBs by using wafer-scale monocrystalline Si with a thickness of 50 μm as the anode (Fig. 12a).…”
Section: Materials For Alloying-type Anodesmentioning
confidence: 99%
“…They concluded that the formation of Li active lithium and eventually, in capacity loss. 84,85 Sternad's group prepared micro-LIBs by using wafer-scale monocrystalline Si with a thickness of 50 mm as the anode (Fig. 12a).…”
Section: Materials For Anodesmentioning
confidence: 99%
See 1 more Smart Citation